2019
DOI: 10.1097/md.0000000000013853
|View full text |Cite
|
Sign up to set email alerts
|

Isolated hypothalamic-pituitary langerhans’ cell histiocytosis in female adult

Abstract: Rationale:Langerhans cell histiocytosis (LCH) is characterized by clonal proliferation of immature dendritic cells, mainly affects children. LCH in adult sellar region is extremely rare. In literature, optimal treatments remain unclear and only a few cases of LCH were treated using surgery. Here, we present a rare case of isolated hypothalamic-pituitary LHC in female adult. We focused on elucidating the clinical manifestations and immunohistochemical features of LCH, and exploring the proper treatment in adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 26 publications
1
12
0
1
Order By: Relevance
“…Interestingly, the LCH lesion was altered from the pituitary to the hypothalamus in the present case. Similar cases have been previously reported, and the courses of MRI findings indicate that the LCH lesion was altered from pituitary or hypothalamus to suprasellar extension ( Table 2 ) ( 5 , 7 , 9 , 10 ). We could not find LCH lesions that extended in a reverse manner (from the hypothalamus to the pituitary) in the literature.…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, the LCH lesion was altered from the pituitary to the hypothalamus in the present case. Similar cases have been previously reported, and the courses of MRI findings indicate that the LCH lesion was altered from pituitary or hypothalamus to suprasellar extension ( Table 2 ) ( 5 , 7 , 9 , 10 ). We could not find LCH lesions that extended in a reverse manner (from the hypothalamus to the pituitary) in the literature.…”
Section: Discussionsupporting
confidence: 85%
“…[ 10 ] Although isolated CNS-LCH is reported, CNS-LCH is mainly diagnosed as multisystemic disease with male predominance. [ 8 11 12 ] Our case also had involvement of the pituitary gland based on MRI findings with central diabetes insipidus.…”
Section: Discussionmentioning
confidence: 74%
“…Tan et al reported a similar case that occurred in the seller area in a 50-year-old woman. Their patient presented with DM-like symptoms, polydipsia, and polyuria, for over 3 months [ 8 ].…”
Section: Discussionmentioning
confidence: 99%